Agenda Setting For Community Midwifery Practice In Public Services In The Environment Of An Islamic Legal Perspective - Deddi Fasmadhy Satiadharmanto; Imam Muhtadin (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2023)
Community Midwifery Practice for 19 days presented by Midwifery Students-Poltekkes Kemenkes Jakarta 3 in the neighborhood of RT 011 RW 05 Malaka Sari Village - Duren Sawit District - East Jakarta. The main problem of this research is how the Authority for Public Services in Family Planning in RT 011 RW 05, Malaka Sari Village, Islamic Law Perspective in several sub-problems, namely: 1). What is the authority of public services for Family Planning and Women's Empowerment in RT 011 RW 05 Malaka Sari Village 2). What is the Islamic Law review of the authority for public services for Family Planning and Women's Empowerment in RT 011 RW 05, Malaka Sari Village? We used Qualitative Field Research or field research using a juridical approach and a sharia approach in implementing Public Services and Women's Empowerment in the RT 011 RW 05 Kelurahan Malaka Sari, East Jakarta. The results of the research show that Community Midwifery Practices by Midwifery Students at the Ministry of Health Jakarta 3 Health Polytechnic on Family Planning and Women's Empowerment in collaboration with the Community Association organization RT 011 RW 05, Malaka Sari Village, East Jakarta, such as information center services and counseling for adolescent and maternal reproductive health. The public service authority carried out by the Head of RT 011 RW 05, Malaka Sari Village, East Jakarta together with Midwifery Students from the Ministry of Health 3 Jakarta Polytechnic on Family Planning and Women's Empowerment from an Islamic Legal Perspective brings goodness to the benefit of society and understanding the needs of women and families. Public Services for Family Planning and Women's Empowerment in the neighborhood of RT 011 RW 05 Malaka Sari Village, East Jakarta, as a social activity for the environment and community to create prosperous and happy families.